Menumbuhkembangkan Minat dan Budaya Menulis Karya Ilmiah di Kalangan Siswa-Siswi SMK Link and Match, Kota Tangerang Selatan, Banten - Syamruddin, Syamruddin; Kamsidik, Kamsidik (Indonesian Journal of Society Engagement, 2024)
Community Service Activities (PkM) in the form of Scientific Writing Writing Training for Link and Match Vocational School Students, South Tangerang City, Banten aims to help students write good and quality scientific papers. Training is carried out using mentoring methods, discussions, workshops and technical guidance (bimtek) in writing scientific papers in accordance with existing standards. The results of the training showed that the abilities of the students who participated in the training were good. Based on a brief assessment carried out by the resource person, it can be concluded that the participants' ability to write scientific papers is good. Even though there are notes for some participants that are still lacking, from the aspect of the standards for writing scientific papers it can be said to have met them. This is certainly very encouraging because the material presented during the training can be digested and understood by participants well, so they can put it into practice when writing scientific papers.  In terms of quantity, the number of scientific papers produced by participants during the training varies. There were participants who were able to write two papers, but there were also those who did not complete one paper. This output will later be used as material and input in perfecting training methods and techniques in subsequent activities.